Dynamic nature of the LVOT following transcatheter mitral valve replacement with LAMPOON: new insights from post-procedure imaging. (2nd May 2021) - Kohli, Keshav; Wei, Zhenglun Alan; Sadri, Vahid; Khan, Jaffar M; Lisko, John C; Netto, Tiffany; Greenbaum, Adam B; Blanke, Philipp; Oshinski, John N; Lederman, Robert J; Yoganathan, Ajit P; Babaliaros, Vasilis C
Abstract: Aims: To characterize the dynamic nature of the left ventricular outflow tract (LVOT) geometry and flow rate in patients following transcatheter mitral valve replacement (TMVR) with anterior leaflet laceration (LAMPOON) and derive insights to help guide future patient selection. Methods and results: Time-resolved LVOT geometry and haemodynamics were analysed with post-procedure computed tomography and echocardiography in subjects ( N  = 19) from the LAMPOON investigational device exemption trial. A novel post hoc definition for LVOT obstruction was employed to account for systolic flow rate and quality of life improvement [obstruction was defined as LVOT gradient > 30 mmHg or LVOT effective orifice area (EOA) ≤ 1.15 cm 2 ]. The neo-LVOT and skirt neo-LVOT were observed to vary substantially in area throughout systole (64 ±  27% and 25 ±  14% change in area, respectively). The peak systolic flow rate occurred most commonly just prior to mid-systole, while minimum neo-LVOT (and skirt neo-LVOT) area occurred most commonly in early-diastole. Subjects with LVOT obstruction ( n  = 5) had smaller skirt neo-LVOT values across systole. Optimal thresholds for skirt neo-LVOT area were phase-specific (260, 210, 200, and 180 mm 2 for early-systole, peak flow, mid-systole, and end-systole, respectively). Conclusion: The LVOT geometry and flow rate exhibit dynamic characteristics following TMVR with LAMPOON. Subjects with LVOT obstruction had smaller skirt neo-LVOT areas across systole. The authors recommend the use of phase-specific threshold values for skirt neo-LVOT area to guide future patient selection for this procedure. LVOT EOA is a 'flow-independent' metric which has the potential to aid in characterizing LVOT obstruction severity. Graphical Abstract: